2011
DOI: 10.1159/000319755
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 Gene Polymorphisms in Tunisian Patients with Inflammatory Bowel Disease

Abstract: Aim: Interleukin (IL)-18 can regulate the Th2-mediated immune response and it may be involved in the pathogenesis of Th1 and Th2 chronic inflammatory diseases. This study sought to detect a possible association between two single nucleotide polymorphisms (SNPs) (–137G/C and –607C/A) in the IL-18 gene promoter region and susceptibility to inflammatory bowel disease (IBD) including Crohn’s disease (CD) and ulcerative colitis (UC) in the Tunisian population. Methods: The (–137G/C and –607C/A) IL-18 polymorphism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Similar to IL-1β, IL-18 has strong pro-inflammatory activities and is essential for the proper regulation of CD4+ T cell function and Th1 cell differentiation (53). Likewise, IL-18 levels are commonly dysregulated in human IBD patients and mutations in the IL-18 gene are associated with UC (54,55). In mice, both IL-18 overexpression and attenuation have been demonstrated to increase pathogenesis in IBD models, which suggest that this cytokine has multiple functions, both positive and negative, during disease progression (6,5658).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to IL-1β, IL-18 has strong pro-inflammatory activities and is essential for the proper regulation of CD4+ T cell function and Th1 cell differentiation (53). Likewise, IL-18 levels are commonly dysregulated in human IBD patients and mutations in the IL-18 gene are associated with UC (54,55). In mice, both IL-18 overexpression and attenuation have been demonstrated to increase pathogenesis in IBD models, which suggest that this cytokine has multiple functions, both positive and negative, during disease progression (6,5658).…”
Section: Discussionmentioning
confidence: 99%
“…Three SNPs in the promoter of the IL-18 gene at positions −656 G/T, −607 C/A and −137 G/C have been identified. These promoter SNPs have been implicated as susceptibility loci for various diseases, including asthma [22], pulmonary tuberculosis [23], inflammatory bowel disease [24], Parkinson’s disease [25], polycystic ovary syndrome [26], type I diabetes [27], and allergic disorders [28]. …”
Section: Discussionmentioning
confidence: 99%
“…57 IL-18 levels are significantly upregulated in subpopulations of patients with IBD, and recent studies revealed an association between SNPs in the promoter region of the human IL-18 gene in UC. 58,59 In mouse models, IL-18 overexpression and IL-18 attenuation have both been shown to enhance IBD pathogenesis. 48,6062 These paradoxical findings suggest that IL-18 has multiple positive and negative functions in IBD pathobiology, and that dysregulation can significantly impact disease pathogenesis and health outcomes.…”
Section: Inflammasome-forming Nlrsmentioning
confidence: 99%